(untitled) (The Research of Medical Science Review, 2025)
Introduction: Lateral epicondylitis primarily arises from repetitive strain due to tasks involving sustained and repeated gripping and/or wrist extension. Various therapeutic modalities have been suggested, with Platelet-rich plasma (PRP) being the most commonly utilized. PRP is an emerging method for tissue healing and regeneration, offering prolonged pain relief effects. Objective: To compare the efficacy of platelet rich plasma and corticosteroid injection in lateral epicondylitis. Material and Methods: The research took place at the Department of Orthopedics KTH Peshawar from September 2024 to January 2025 as a Randomized Controlled Trial. The total patient sample required 80 subjects who received equal distribution into two distinct groups. A total number of 40 patients underwent either corticosteroid or PRP treatment procedures. The treatment procedure involved injecting 2 mL of PRP solution combined with 1 mL of prilocaine hydrochloride (20 mg/mL) into the lateral epicondyle area using a 21G injector according to the affected spot with maximum pain. Betamethasone was the medication used during the corticosteroid group injections. A systematic follow-up check occurred at the second week post-injection. Visual analog scale (VAS)scores less than 3 were considered an effective result after two weeks of treatment based on the evaluation through VAS. A statistical analysis took place on the SPSS software system. Results: Our study population entailed of 53.8% males and 46.3% females. PRP was significantly (p = 0.025) more effective than corticosteroids, with 65.0% of patients in the PRP group achieving positive outcomes compared to 40.0% in the corticosteroid group. Stratification analysis reflected that PRP was significantly (p=0.040) more effective in younger patients, those having BMI >29kg/m2 (p=0.004) and belonged to rural areas (p=0.049). Conclusion: PRP is a more effective treatment option for lateral epicondylitis compared to corticosteroids, particularly in younger patients, those with higher BMI, and those from rural areas.